Kajian Literatur tentang Model Mitigasi Bencana Lanskap Pesisir di Kota Banda Aceh - Hasan, Zainuddin; Mahidin; Achmad, Ashfa; Irwansyah, Mirza; Aufaraihan, Nabilah (Jurnal Lanskap Indonesia, 2025)
Disaster mitigation is a disaster risk management strategy that can help reduce and minimize disaster impacts. Spatial planning policy is essential for disaster mitigation as it will affect the distribution of development and the vulnerability of communities to disasters. Communities living in coastal settlements are very vulnerable to disasters, so a spatial-based disaster mitigation strategy will provide an appropriate strategy for activities in coastal settlements, especially in the coastal areas of Banda Aceh City. The purpose of this research is to evaluate the role of spatial planning policies in supporting disaster mitigation, as well as to examine the implementation of mitigation strategies involving community participation and the use of GIS technology. This research used qualitative methods with a literature review approach to analyze, synthesize, and identify trends, gaps, and recommendations from various literatures related to spatial-based disaster mitigation, community participation, and GIS technology. The results of this study showed that spatial planning policies played an important role in reducing disaster risk, with a focus on proper zoning and protection of vital infrastructure. Adaptation strategies such as mangrove planting and effective evacuation routes were key to mitigation. Community participation and the use of GIS technology helped identify risks and develop hazard maps. However, challenges such as lack of policy socialization and limited spatial data remain obstacles to optimal implementation.